Genotypic diversity in vegetable amaranth for antioxidant, nutrient and agronomic traits - Sarker, Umakanta; Islam, Md. Tofazzal; Rabbani, Md. Golam; Oba, Shinya (The Indian Journal of Genetics and Plant Breeding, 2017)
In this investigation, magnitude of genetic divergence wasstudied in 25 vegetable amaranth using D2 statistics. Thegenotypes were grouped into 5 clusters with the highestnumber of genotypes (10) in cluster V. High inter-clusterdistance indicated that genotypes of cluster III were fardiverged from the genotypes in cluster I, II and IV,respectively. The PCA indicated prominent contributionof protein, foliage yield, leaf area and Zn content towardstotal divergence. Cluster I and Cluster III could be consideredfor excellent antioxidant and nutrients and high foliageyield. Cluster II for nutrients, cluster IV for antioxidant andnutrients and cluster V for antioxidant, nutrients, andfoliage yield. Based on inter-cluster distance, intra-clusterand scatter diagram, the genotypes AA28, AA15, AA19,AA26, AA9 and AA17 would be potential genotypes forgenerating transgressive segregants.